Sintesis Senyawa Kalkon (E)-1-(4-Klorofenil)-3-P-Tolilprop-2-En-1-On dan Uji Toksisitasnya - Brahmana, Eti Meirina (Prosiding SNPBS (Seminar Nasional Pendidikan Biologi dan Saintek), 2016)
Halogen substituted analogoues compounds chalcone, (E)-1-(4-klorofenil)-3-p-tolilprop-2-en-1-on, was synthesized from 4-metyl benzaldehyde as aldehydes with 4-chloroacetophenone as ketones by using aldol condensation reaction. The compound resulted rendement with value of 87,51% and characterized by using UV, IR, MS, and 1HNMR. Toxicity tests using Brine Shrimp Lethality Test (BSLT) showed that those compounds have a potency as anticancer agent with LC50 value 39,8 μg/mL.